A MODEL PEMBELAJARAN ROLE PLAYING DENGAN GAME DIGITAL TERHADAP SIKAP DAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - Risky Muslikasari; Rusnilawati Rusnilawati (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2023)
The purpose of this research is to describe the differences in problem-solving skills and attitudes towards mathematics learning between the use of role-playing learning models with digital games and mathematical learning models. An experimental method was employed in this research with a quasi-experimental design, involving randomly selected control and experimental groups. The results of hypothesis testing indicate that (a) the Sig. (2-tailed) value is 0.000, meaning that the Sig. (2-tailed) value < 0.05, thus it can be concluded that H0 is rejected, and Ha is accepted, implying that students' attitudes towards mathematics learning using the role-playing learning model with digital games are better than before its implementation. (b) The t-test results show a t-value of 2.472 with degrees of freedom (df) of 42 and a significance value of t-table 5% is 2.01. Hence, it can be inferred that the t-value (2.474) > t-table (2.02), which can be interpreted as H0 being rejected and Ha being accepted, indicating that problem-solving skills in mathematics learning with the role-playing learning model with digital games are better than before its implementation. (c) The F-test for problem-solving skills (5.866) > F-table (4.07) and the F-test for attitudes (6.120) > F-table (4.07). Thus, the conclusion is that H0 is rejected, and Ha is accepted, signifying that attitudes and problem-solving skills in mathematics learning after using the role-playing learning model with digital games are better than the cooperative learning model with fraction board media.